Modelling Economic Growth Based on Economic Freedom and Social Progress - Asandului, Laura; Iacobuta, Andreea; Cautisanu, Cristina (European Journal of Sustainable Development, 2016)
Economic growth is one of the most widely studied issues in the specialised literature. Economic growth highlights those changes that occur in enhancing macroeconomic results that are not expressed independently, but in close connection with its determinants. This article aims at modelling the economic growth of the member states of the European Union in relation to the economic freedom index and the index of economic progress. We consider the following objectives: the study of the intensity of relationships between GDP per capita and index of economic freedom on one hand, and social progress index on the other; modelling growth relative index of economic freedom and social progress index for the EU Member States Union. To investigate these topics, we have used descriptive analysis, analysis of variance, correlation analysis, and multiple regression analysis. We have developed a multiple regression model to study the influence that the index of economic freedom and of the social progress index have on the growth rate of GDP per capita in countries which have the status of member the European Union. Through variance analysis, we have concluded that there are significant differences among the average GDP per capita in the European countries according the membership of the European Union. Keywords: modelling economic growth, economic freedom, social progress, european countries